Selective Detection of Acetone Vapor Using Hydrophobized Pillared Carbon Thin Films - Matsuo, Yoshiaki; Araki, Masanobu (Frontiers in Materials, 2017)
Pillared carbon thin films were prepared from the thermal reduction of graphite oxide silylated with octyltrichlorosilane and then dimethyldichlorosilane. The interlayer spacing of the resulting pillared carbon thin film was 1.29 nm and it contained hydrophobic Si-CH3 groups, excluding Si-OH ones. The resistance of it increased during the exposure to acetone vapor, while it was unchanged when it was exposed to the water vapor. Moreover, in the presence of water vapor the resistance changed in a similar manner.